2017
DOI: 10.1159/000479418
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein B Suppresses Lung Cancer Progression by Inhibiting Secretory Phospholipase A2 Activity and Arachidonic Acid Production

Abstract: Background/Aims: Radiotherapy is applied to patients with inoperable cancer types including advanced stage non-small cell lung cancer (NSCLC) and radioresistance functions as a critical obstacle in radiotherapy. This study was aimed to investigate the mechanism of radioresistance regulated by surfactant protein B (SP-B). Methods: To investigate the role of SP-B in radioresistance, ΔSFTPB A549 cell line was established and SP-B expression was analyzed. In response to ionizing radiation (IR), the change of SP-B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…There are data, however, which suggest a favorable role of surfactant in primary lung cancer. Recent studies suggest that surfactant proteins A and B are able to suppress the progression in NSCLC (45,46), possibly through interaction with immune cells (46,47) or by reducing the activity of EGFR and thereby acting in a similar manner to tyrosine-kinase inhibitors (48). The role of NAPSA in lung cancer is much less established, but recent studies suggest that NAPSA could have a supportive function with regards to the effect of EGFR tyrosine kinase inhibitors (49).…”
Section: Discussionmentioning
confidence: 99%
“…There are data, however, which suggest a favorable role of surfactant in primary lung cancer. Recent studies suggest that surfactant proteins A and B are able to suppress the progression in NSCLC (45,46), possibly through interaction with immune cells (46,47) or by reducing the activity of EGFR and thereby acting in a similar manner to tyrosine-kinase inhibitors (48). The role of NAPSA in lung cancer is much less established, but recent studies suggest that NAPSA could have a supportive function with regards to the effect of EGFR tyrosine kinase inhibitors (49).…”
Section: Discussionmentioning
confidence: 99%
“…Although this has not been reported in other cancer types, further studies are required to determine how phosphatidylinositol synthase might regulate EMT in cancer cells. Eicosanoids are bioactive lipids derived from arachidonic acids and they have been suggested as promising targets for anti-cancer therapies [108]. Eicosanoids are produced by cyclooxygenase (COX), lipoxygenase (LOX), and cytochrome P450 (CYP450) from arachidonic acid and each lipid derivative activates various cellular signaling pathways [109].…”
Section: Lipid Metabolism In Emtmentioning
confidence: 99%
“…Radiation therapy is known to be an important approach for the treatment of NSCLC, but the obstacle of radiation resistance has a negative effect on the survival of patients with NSCLC [23]. Recently, several studies have suggested that miRNAs play a role in the radiation resistance of NSCLC by interacting with tumor-related genes [24, 25].…”
Section: Discussionmentioning
confidence: 99%